1982
DOI: 10.1128/jcm.15.2.312-319.1982
|View full text |Cite
|
Sign up to set email alerts
|

Porcine pararotavirus: detection, differentiation from rotavirus, and pathogenesis in gnotobiotic pigs

Abstract: Some characteristics of a newly recognized porcine enteric virus are described. Tentatively, the virus was referred to as porcine pararotavirus (PaRV) because it resembled rotaviruses in respect to size, morphology, and tropism for villous enterocytes of the small intestine. However, it was antigenically distinct from porcine, human, and bovine rotaviruses and reoviruses 1, 2, and 3, and the electrophoretic migration pattern of PaRV double-stranded RNA was distinct from the electrophoretic migration patterns o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
115
1

Year Published

1985
1985
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 191 publications
(121 citation statements)
references
References 14 publications
4
115
1
Order By: Relevance
“…A bovine rotavirus-like agent (RVLA) identified in our laboratory was morphologically identical to rotavirus but differed antigenically and in the double-stranded ribonucleic acid electropherotype (63). However, this RVLA did not react antigenically or have a similar RNA electropherotype to a different RVLA which we previously identified in pigs (8,60), suggesting the existence of several antigenically distinct categories of RVLA. Whether the bovine and porcine RVLA that we identified share common antigens with recently described RVLA from other species (10) is unknown.…”
Section: Bovine Enteric Diarrheal Viruses: Description and Antigenic contrasting
confidence: 59%
“…A bovine rotavirus-like agent (RVLA) identified in our laboratory was morphologically identical to rotavirus but differed antigenically and in the double-stranded ribonucleic acid electropherotype (63). However, this RVLA did not react antigenically or have a similar RNA electropherotype to a different RVLA which we previously identified in pigs (8,60), suggesting the existence of several antigenically distinct categories of RVLA. Whether the bovine and porcine RVLA that we identified share common antigens with recently described RVLA from other species (10) is unknown.…”
Section: Bovine Enteric Diarrheal Viruses: Description and Antigenic contrasting
confidence: 59%
“…The processed nasal swab fluid was tested for rotavirus or coronavirus using a cell culture immunofluorescence (CCIF) test (Saif et al, 1986;Bohl et al, 1982). Feces or rectal swab samples were processed as described previously and tested for presence of rotavirus using CCIF and ELISA assays (Bohl et al, 1982;Saif et al, 1986), or for coronavirus using immune electron microscopy on 10% fecal suspensions (IEM, Saif et al, 1977).…”
Section: Assays For Virus Sheddin Bmentioning
confidence: 99%
“…The recent identification of the atypical rotaviruses has been of considerable interest. At least three different strains have been studied in pigs: a Belgian isolate (Debouck and Peusaert, 1979), one from the United Kingdom (Bridger et al, 1982), and one from the United States (Saif et al, 1980;Bohl et al, 1982). A comparison of the U.K. and U.S.A. strains of atypical porcine rotaviruses revealed that they were unrelated as shown by cross-immunofluorescence studies (Pedtey et al, 1983).…”
Section: Discussionmentioning
confidence: 99%
“…However, the same polypeptide also carries one of two subgroup specificities (I or II) which is easily detected by using subgroup-specific monoclonal antibodies (Greenberg et al, 1983). Neither the group-common nor the subgroup-specific antigenicities are found on some "atypical" rotaviruses ("pararotaviruses") which have been isolated from different animal species, including pigs (Bohl et al, 1982;Bridger et al, 1982). Subgroup antigens do not appear to be related to neutralization or immunoprotection, but they provide useful markers for epidemiological studies.…”
Section: Introductionmentioning
confidence: 99%